BELIEF IN GOD BY INTUITIVE KNOWLEDGE IN MULLÄ€ á¹¢ADRÄ€â€™S PHILOSOPHY : (A CRITIQUE TO ATHEISTIC EVIDENTIALISM) - Hakimelahi, Abdolmajid; Hamdani, Basrir (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2016)
The epistemological approach of evidentialism maintains that a belief must have sufficient evidence in order to be rationally justified. The belief in God is no exception, it must pass as well the litmus test of evidence as a measure of its rational justification. But what counts as evidence? Responding to this question and identifying the nature of the evidence that can be used to justify belief has become a point of contention among philosophers. While some evidentialists have denied the possibility of evidence for the belief in God, others have attacked the very basis of the evidentialist claim by promoting belief in God without evidence. The following paper aims at proposing an alternative way or approach to argue and to justify belief in God, that is, intuitive knowledge. To excute this aim, this paper tries at first to describe briefly those two currents of thought and, further, examines and criticizes them by discussing and analyzing the notion of innate concepts and presentational knowledge as known by an intuitive knowledge based on MullÄ á¹¢adrÄâ€™s view. According to some philosophers, this type of knowledge, presentational knowledge, can be included as â€œevidenceâ€ even from the evidentialist point of view which does not limit evidence to conceptual knowledge. By this, critical analysis will be applied here as a method to conduct the research.